Preliminary development and piloting of a user‐generated routine outcome measure in a children and young people's counselling service. Issue 3 (8th July 2016) - Perry, Sarah; Carpenter, Simon; ,
Abstract: Background: Routine outcome monitoring has become a major focus of children and young people's mental health and counselling services in the United Kingdom, in the spirit of increasing user participation and delivering evidence‐based practice. In this pilot project, a group of young people were supported as co‐researchers to explore the ways in which counselling and therapy services measure their effectiveness. Aims: To explore young people's views of appropriate outcome measures of the effectiveness of therapy and to develop a novel user‐generated questionnaire. Methodology: The project was informed by co‐operative enquiry and participation research, whereby the co‐researchers were also co‐participants. Eight young people designed and created a novel questionnaire to assess the effectiveness of therapy and service satisfaction. The questionnaire focused explicitly on the actual benefits of therapy to young people, as perceived by themselves and expressed in their own words. This questionnaire was subsequently piloted with 66 participants attending a specialist counselling service for children and young people who have experienced abuse. Results: A reasonable spread of ratings to the individual items and few 'Don't know' responses suggested that the items were easy to understand and the rating scale functional. Total scores were positively skewed. Implications: Although there are challenges for co‐operative enquiry and meaningful participation research with young people, the limitations of current outcome evaluation require the development of more relevant and sensitive measures of children and young people's experiences of therapy.